Distribution, dispersion and regulation in a population of the Common Shelduck - Hori, John (Wildfowl, 1987)
A breeding population of Common Shelduck Tadorna tadorna was re-studied after an interval of sixteen years. Generally distribution is limited by narrow territorial preference, but given habitat modification, adaptation can relieve this constraint. Dispersion is effected by territorial and commune behaviour. Communes provide information transfer on nesting locations and experience on hole nesting, stimulate achievement of breeding condition, and, through multiple nesting, regulate breeding output. Communes involve experienced and inexperienced birds. The latter are probably aged from two to four years and many, probably the youngest, lay only small numbers of eggs, sometimes one. Only a fraction of the population used single nests. Increased density in the 1980s resulted from a larger population and habit changes. This caused different outcomes from multiple nesting. It is hypothesized that behaviour of inexperienced adult females at multiple nests causes density dependent regulation by varying hatching success. Most young females may not be capable of incubating. At low densities multiple nests could provide for incubation of their eggs at success rates comparable with or greater than single nests. At high densities the activity of young females is disruptive and can cause total failure.